2017
DOI: 10.1038/labinvest.2017.26
|View full text |Cite
|
Sign up to set email alerts
|

Increased vasohibin-1 expression is associated with metastasis and poor prognosis of renal cell carcinoma patients

Abstract: The microvascular density detected by markers of endothelial cells (ECs), such as CD31 and CD34, is considered to be a biomarker for angiogenesis, and it is generally associated with the malignant potential of solid tumors. However, there is a conflicting relationship between the microvascular density and prognosis in clear-cell renal cell carcinoma (ccRCC) patients. It may be explained by the suggestion that the microvascular density cannot fully reflect the angiogenic activity in ccRCC, as the markers of ECs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 36 publications
(77 reference statements)
1
23
0
Order By: Relevance
“…Receiver operating characteristic curve analysis was undertaken to determine the area under the curve, and the optimal cut-off value was taken as the farthest point from the diagonal line of the curve. 4 Cases in which the PD-1-positive TIIC score, PD-L1-positive TIIC score, or PD-L1positive tumor score was higher than the cut-off values were defined as high cases, and those with percentages lower than the cut-off values were defined as low cases. The log-rank test and Kaplan-Meier method were used for survival analyses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Receiver operating characteristic curve analysis was undertaken to determine the area under the curve, and the optimal cut-off value was taken as the farthest point from the diagonal line of the curve. 4 Cases in which the PD-1-positive TIIC score, PD-L1-positive TIIC score, or PD-L1positive tumor score was higher than the cut-off values were defined as high cases, and those with percentages lower than the cut-off values were defined as low cases. The log-rank test and Kaplan-Meier method were used for survival analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analysis of the ccRCC tissues without pretreatment was carried out by dividing them into the following groups: groups of low stage (pT1 and pT2) and high stage (pT3 and pT4) or groups of low grade (grades 1 and 2) and high grade (grades 3 and 4). Receiver operating characteristic curve analysis was undertaken to determine the area under the curve, and the optimal cut‐off value was taken as the farthest point from the diagonal line of the curve . Cases in which the PD‐1‐positive TIIC score, PD‐L1‐positive TIIC score, or PD‐L1‐positive tumor score was higher than the cut‐off values were defined as high cases, and those with percentages lower than the cut‐off values were defined as low cases.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…studies were identified as meeting our inclusion criteria [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], whose detailed information was shown in Table 2. The VASH1 relatively-low expression group (1225 individuals; 52.8%) was regarded as the control group.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%